The Potency of Social Constructivism on Classroom Productivity in Universities - Bunmi Isaiah Omodan (Indonesia Approach Education, 2022)
Various indications, including literature, have confirmed that university classrooms are still mostly inactive and undemocratic, dominated by instructors and lecturers. That is, little or no atmosphere is created for the student to be a socially active participant in generating knowledge which appears to have affected their sociality in the university and their lives after their university education. Some university lecturers still use a traditional or a systematic colonized way of teaching. This study responded by proposing unabridged Social Constructivism (SC) to create socially active university students towards becoming productive and active citizens. This was done by answering a general question: How can SC be projected in the university classroom to create active and productive students? This study was located within a transformative paradigm in order to transform students’ inactiveness in the process of generating knowledge. Conceptual analysis was used to design the study. This was done within the principle of thematic analysis by arranging SC's assumptions into themes and making sense of them. The study thus presents that SC possesses the acumen to assist lecturers in ensuring that their classrooms are socially active towards student productivity both in the schools and in the field of work.